First review of recent records of sturgeons and paddlefishes (Acipenseriformes) in the Danube River basin in Slovenia - Marijan Govedič; Thomas Friedrich (Natura Sloveniae)
We present recent records of sturgeons and paddlefishes from the rivers in Danube basin in Slovenia after 2000. Strictly, only confirmed and unambiguous records (specimen, picture) were taken into account. The sterlet and the Siberian sturgeon have been occasionally found in rivers and Russian sturgeons in gravel pits, while sterlets, Siberian sturgeons, Russian sturgeons and the paddlefish are still farmed in some ponds. The Siberian sturgeons were released in the Mura and Sava River in 2016, but the species is as »exotic pet fish« present in more water bodies. The presence of sturgeons in gravel pits is unknown. The Siberian sturgeon can be relatively easily misidentified with the sterlet, so the catches in the Mura and Sora Rivers in 2009 were misidentified as sterlet, while the Siberian sturgeon was actually captured. The last sterlet in Slovenian rivers was captured in the Drava River in 2001, and even this individual had probably been released in Austria. The occurrence of sturgeons in Slovenian rivers in the last eighteen years does not seem to be connected with migration and revival of natural populations in the lower part of the Drava and Sava Rivers.